Entrepreneurial Education and Entrepreneurial Culture among University of Cape Coast Students in Ghana - Nina Afriyie; Rosemond Boohene (Athens Institute for Education and Research, 2014)
Currently the Ghanaian economy's capacity to absorb new recruits into the formal sector has fallen. Therefore, for young people to escape the incidence of not getting employed after school, active intervention is necessary. There is an urgent need for young people to be trained and educated in the field of entrepreneurship especially university students. This study examined the link between entrepreneurship education and entrepreneurial culture among university students in Ghana. A sample of 203 students was randomly selected from the three schools in University of Cape Coast Ghana. Correlation coefficient was the parametric statistical tools used to test the association in the study. Entrepreneurial culture was measured using entrepreneurial mindset, business startup motives and entrepreneurial orientation. Four dimension were used under entrepreneurial orientation; proactiveness, perseverance, innovativeness and risk taking propensity. A significant relationship was observed between entrepreneurship education and entrepreneurial culture. This study therefore argues that entrepreneurship education will equip the students with the skills with which to be self-reliant. Results again holds the implication for among others, that if entrepreneurship education is made core and studied by all students irrespective of the areas of specialization, will help inculcate the culture of entrepreneurship in University of Cape Coast students leading to they being job creators rather than job seekers, and in the long term effect, graduate unemployment will be reduced.